THE ROLE OF FRAUD HEXAGON IN DETECTING FRAUDULENT FINANCIAL REPORTING: STUDY ON FINANCIAL SECTOR COMPANIES - Ningrum, Mamlucha Fitriya; Abdani, Fadlil (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
This study aims to analyze the role of fraud hexagon on fraudulent financial reporting in the financial sector companies. Financial statements assess an entity's performance and provide important information for stakeholders. However, despite being required to be transparent, financial statements remain vulnerable to manipulation (fraudulent financial reporting) to attract investors, especially in the financial services industry. Information asymmetry theory describes the imbalance of information between parties, while the fraud hexagon extends previous fraud theory with six factors: pressure, opportunity, rationalization, capability, arrogance, and collusion. This study uses logistic regression on the financial sector companies listed on the IDX. The investigation shows that pressure (financial targets) has a negative effect on fraudulent financial reporting, while variables such as opportunity, rationalization, capability, arrogance, and collusion have no significant effect on fraudulent financial reporting.